Population demography of Oldham’s leaf turtle (Cyclemys oldhamii) in protected and disturbed habitats in Thailand - Sengvilay Seateun; Nancy E. Karraker; Bryan L. Stuart; Anchalee Aowphol (PeerJ, 2019)
Background Freshwater turtle populations are vulnerable to a range of human activities because of particular life history attributes, and anthropogenic impacts can cause shifts in demographic traits, including survival, density and population structure. Asian freshwater turtles have undergone dramatic population declines in recent decades principally because of collection for food, pet, and traditional medicine markets. Despite this, few studies have been conducted on the population demography of these turtles, thereby limiting our understanding of population trends and the development of conservation actions. Oldham’s leaf turtle (Cyclemys oldhamii) is one of the most commonly traded turtles in Asian markets, but previous published studies have focused solely on systematics. Methods We conducted a mark-recapture study of C. oldhamii at three sites in northeastern Thailand—a protected stream, a degraded stream, and human-constructed ponds—and evaluated differences in survival, density, population structure, and sexual dimorphism among sites. Results We captured 77 turtles at the protected stream, 67 at the constructed ponds, and two in the degraded stream. Survival was 12% lower and density was 35% lower in the constructed ponds than in the protected stream. Size class structure was skewed toward smaller individuals at the constructed ponds, and both sites exhibited subadult-skewed age class structure. Sex ratios were not statistically different than 1:1 at either site and did not differ between sites. We did not document sexual dimorphism in either population. Discussion Explanations for lower survival, lower densities, and skewed size class structure at the constructed ponds include collection for consumption or Buddhist prayer release locally, collection for illegal export from Thailand, predation by domestic dogs associated with humans living nearby, or lower habitat quality. Evidence from our study suggests that collection, either for local use or export, is the most likely explanation for differences in demographic characteristics between the two sites. The information gained from this study may contribute to a status assessment for C. oldhamii and development of conservation actions should they become necessary to protect populations in Thailand.